A Bibliometric Review of Research on International Students’ Mental Health: Science Mapping of the Literature from 1957 to 2020 - Cao, Quoc Thai (2022)
The mental health of university students is not only a predominant topic for psychology and education researchers but also a source of interest for policymakers and various stakeholders. Although there has been a lot of research on higher education students’ mental health, we have little understanding on the mental health of international students (MHIS). Despite their distinctive characteristics compared to native students, the mental health issues of international students only started receiving attention very recently. So far, the literature on this topic lacks a comprehensive overview of its sub-topic and trending issues. By using bibliometric analysis, this research aims to fulfil this gap and provide a review of the extant literature about MHIS. Specifically, this study aims to (i) draw the growth trajectory and geographic distribution of the literature on MHIS; (ii) identify the documents and authors that have the greatest impact, generally and locally, within the major topic clusters of the literature on MHIS; and (iii) identify the most researched keywords in the literature on MHIS over time. The results have shown that academic documents about international students’ mental health are increasing in number and becoming more extensive content-wise. The research’s findings provide implications for stakeholders and identifies some prominent research avenues for the future.